"Assessment and Management of Poor Performance in Mathematics: Using Academic Self-Efficacy and Cognitive Restructuring Techniques." (2016)
"The study investigated the effect of cognitive restructuring therapy on poor performance in Mathematics among Secondary School Students. Sixty Senior Secondary School (SSS 11) Students were used for the study. The research adopted a pretest, posttest and control group quasi experimental design with a 2x2x2 factorial matrix. Two schools were randomly selected from two different Local Government Areas in Ibadan. 30 participants each were randomly selected for the treatment and control group from the two selected schools. The major instruments used for the study were Academic Self-Efficacy Scale (ASES) r= .80 and Mathematic Performance Test (MPT) r = .77. The data were analysed with the aid of Analysis of Covariance (ANCOVA) tested at the 0.05 level of significance. The finding indicates that the participants exposed to Cognitive Restructuring Therapy showed a significant improvement in their mathematics performance than those in control group. It was also found that Academic Self-Efficacy when properly managed has a significant effect on mathematics performance of students. It is recommended that Cognitive Restructuring Therapy should be used by the Counselling Psychologists to intensify their effort to make use of the intervention in their strategies for counselling "